Silicon-carbon composite, method for preparing the same, and secondary battery containing the same
Patent Information
- Application Number
- CN202280007367.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2042-08-26
AI Technical Summary
[0003]二次电池中通常使用石墨作为负极材料,但石墨的理论容量较低(372mA·h/g),已无法满足对具有更高体积容量、能量密度的二次电池的需求
Smart Images

Figure CN117957667B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a silicon-carbon composite material, its preparation method, and a secondary battery containing the same. Background Technology
[0002] In recent years, rechargeable batteries have been widely used in various electronic products and electric vehicles due to their high power density and volumetric capacity. However, with the significant development and widespread application of rechargeable batteries, higher requirements have been placed on their volumetric capacity, energy density, and cycle life.
[0003] Graphite is commonly used as the anode material in secondary batteries, but its theoretical capacity is relatively low (372 mA·h / g), which is insufficient to meet the demand for secondary batteries with higher volumetric capacity and energy density. Silicon-based materials, due to their extremely high theoretical capacity (4200 mAh / g) and low lithium intercalation potential, have become more ideal anode materials for secondary batteries. However, silicon's extremely low conductivity and large volume expansion limit its application. Therefore, improving the electrochemical performance of secondary batteries using silicon-based materials as anode materials has become an urgent technical problem to be solved. Summary of the Invention
[0004] This application is made in view of the above-mentioned technical problems, and its purpose is to provide a silicon-carbon composite material with good electrical conductivity and structural stability, which enables the secondary battery to have good cycle life while improving the energy density of the secondary battery.
[0005] In a first aspect, this application provides a silicon-carbon composite material, the silicon-carbon composite material comprising a porous carbon matrix and silicon-based particles; the porous carbon matrix includes a plurality of channels with a width of 5nm-50nm, the silicon-based particles are distributed in the channels, and the porous carbon matrix satisfies: 1.0×10 -7 ≤V 总 / S 总 ≤10×10 -7 Among them, S 总 The total surface area occupied by the channels with a width of 5nm-50nm, measured in units of ×10. 4 cm 2 / g;V 总 The total pore volume occupied by the channels with a width of 5nm-50nm, measured in cm. 3 / g.
[0006] The silicon-carbon composite material provided in this application has a porous carbon matrix with multiple elongated channels, forming a cross-linked three-dimensional network structure. Silicon particles are distributed within these cross-linked channels. On one hand, the three-dimensional network structure of the porous carbon matrix can accommodate and restrict the expansion of silicon particles, mitigating the damage to the composite material structure caused by silicon particle expansion during battery cycling, thereby improving the cycle stability of the composite material in the battery. On the other hand, the specific pore distribution and structure of the porous carbon matrix help silicon occupy the pores in the carbon skeleton and disperse within the carbon material, enabling efficient electron transport through the highly conductive cross-linked carbon skeleton. This allows the silicon-carbon composite material to have both high specific capacity and good conductivity, which helps reduce battery polarization when applied to batteries.
[0007] In some embodiments, 1.0 ≤ V 总 / S 总 ≤10, optionally, 2.0≤V 总 / S 总 ≤5.0, unit: 10 -7 cm.
[0008] In some embodiments, 10≤S 总 ≤50, optionally, 1≤S 总 ≤30, unit: ×10 4 cm 2 / g.
[0009] In some embodiments, 0.002 ≤ V 总 ≤0.250, optionally, 0.004≤V 总 ≤0.200, unit: cm 3 / g.
[0010] In the embodiments of this application, the porous carbon matrix has elongated channels with a width of 5nm-50nm. The porous carbon matrix satisfying the above conditions constitutes a three-dimensional cross-linked network structure, and contains at least two interconnected channels. This allows the porous carbon matrix to possess both a three-dimensional network structure and a large specific surface area, providing sufficient space and volume for silicon-based particles to distribute on it. The channel structure in this porous carbon matrix also has a large volume, capable of accommodating and limiting the expansion of silicon-based particles during battery cycling, thereby maintaining the structural stability of the silicon-carbon material during battery cycling.
[0011] In some embodiments, the powder resistivity of the porous carbon matrix at a pressure of 4 MPa is 1 Ω / cm-300 Ω / cm, optionally 1 Ω / cm-100 Ω / cm.
[0012] The silicon-carbon composite material provided in this application has a porous carbon matrix with extremely low powder resistivity. A carbon skeleton with good conductivity is constructed through this porous carbon matrix, so that the silicon-carbon composite material obtained by combining the carbon skeleton and silicon-based particles also has good conductivity.
[0013] In some embodiments, the size of the silicon-based particles is less than or equal to 20 nm, preferably 2 nm to 10 nm.
[0014] In some embodiments, the volumetric particle size distribution D of the porous carbon matrix v50 ≤10μm, optionally 5≤D v50 ≤10μm; and / or the volumetric particle size distribution D of the porous carbon matrix v90 ≤20μm, optionally 10≤D v90 ≤15μm.
[0015] In some embodiments, the content of the silicon-based particles in the silicon-carbon composite material is 25%-65%, optionally 35%-45%.
[0016] In the embodiments of this application, by controlling the content of silicon-based particles in the silicon-carbon composite material within a suitable range, the problem of low specific capacity due to excessively low silicon content can be effectively avoided; or the problem of excessively high silicon content leading to excessive silicon-based particles damaging the excellent conductivity of the carbon skeleton can be avoided. Thus, this helps to improve the specific capacity of the silicon-carbon composite material while also contributing to improving the cycle stability of the silicon-carbon material in batteries.
[0017] In some embodiments, the powder resistivity of the silicon-carbon composite material at 12 MPa pressure is R ≤ 300 Ω / cm, optionally 1.1 Ω / cm-200 Ω / cm; and / or the powder resistivity of the silicon-carbon composite material at 16 MPa pressure is R ≤ 200 Ω / cm, optionally 1 Ω / cm-100 Ω / cm.
[0018] In the embodiments of this application, thanks to the three-dimensional network structure of the porous carbon matrix with mutual cross-linking, silicon particles are uniformly distributed inside the matrix. The silicon-carbon composite material has a small powder resistivity, in other words, it has good conductivity. This allows the silicon-carbon composite material to have a high specific capacity in the battery while also having good structural stability and cycle stability.
[0019] In some embodiments, the silicon-carbon composite material satisfies one or more of the following (1)-(6): (1) the volumetric particle size distribution of the silicon-carbon composite material is Dv10≤5μm, optionally 3≤Dv10≤5μm; (2) the volumetric particle size distribution of the silicon-carbon composite material is Dv50≤10μm, optionally 5≤Dv50≤8μm; (3) the volumetric particle size distribution of the silicon-carbon composite material is 10≤Dv90≤20μm, optionally 10≤Dv90≤15μm; (4) the particle size distribution of the silicon-carbon composite material satisfies: (Dv90-Dv10) / Dv50≤1.8, optionally 1.4≤(Dv90-Dv10) / Dv50≤1.6; (5) the compaction density of the silicon-carbon composite material under 2MPa pressure is 1g / cm³. 3 -1.5g / cm 3 Optionally, it can be 1.1 g / cm³. 3 -1.3g / cm 3 (6) The specific surface area of the silicon-carbon composite material is 2m². 2 / g-10m 2 / g, optionally 3m 2 / g-7m 2 / g.
[0020] In some embodiments, the peak value of the X-ray diffraction (XRD) peak of the carbon-based composite material between a diffraction angle of 28°-29° is denoted as P1, and the peak value of the XRD peak of the silicon-based particles between a diffraction angle of 42°-45° is denoted as P2, then 2≤P1 / P2≤4; optionally, 600≤P1≤800; optionally, 200≤P2≤400.
[0021] In a second aspect, a method for preparing a silicon-carbon composite material is provided, the method comprising: mixing a substrate and a pore-forming agent in a solvent to obtain a first mixture; treating the first mixture at high temperature to obtain a porous carbon matrix; and depositing silane gas onto the porous carbon matrix by chemical vapor deposition to obtain the silicon-carbon composite material.
[0022] In some embodiments, the substrate includes at least one of sugar and resin; optionally, the sugar includes at least one of glucose, sucrose, fructose, starch, amylopectin, amylose, lignin, dextrin, and maltodextrin; optionally, the resin includes at least one of linear phenolic resin, soluble phenolic resin, epoxy resin, and polyurethane.
[0023] In some embodiments, the pore-forming agent includes at least one of sodium chloride, potassium chloride, zinc chloride, sodium carbonate, and potassium carbonate.
[0024] In some embodiments, the mass ratio of the substrate to the pore-forming agent is 1:5-10:1, and optionally 2:1-5:1.
[0025] In the embodiments of this application, the amount of porogen is determined according to the amount of substrate. This effectively avoids the situation where insufficient porogen fails to generate enough gas to form a pore structure of 2nm-10nm; or avoids the situation where excessive porogen leads to violent local reactions, rapid gas generation, and large-sized pores or voids. Therefore, by controlling the mass ratio of substrate to porogen within a suitable range, it is possible to ensure that the prepared porous carbon matrix has a three-dimensional network structure formed by the cross-linking of pores of 5nm-50nm.
[0026] In some embodiments, the solvent comprises water or an alcohol, wherein the alcohol comprises at least one of methanol, ethanol, ethylene glycol, polyethylene glycol, glycerol, isopropanol, or a polyol.
[0027] In some embodiments, the mass ratio of the substrate to the solvent is 1:100-10:1, and optionally 1:2-10:1.
[0028] In the embodiments of this application, the amount of solvent is determined according to the amount of substrate. This effectively avoids situations where insufficient solvent results in excessive viscosity of the first mixture, preventing timely dispersion of gas generated by the pore-forming agent and leading to larger or longer pore sizes; or where excessive solvent results in excessive viscosity of the first mixture, causing rapid gas expulsion and pore-forming failure. Therefore, by controlling the mass ratio of substrate to solvent within a suitable range, the quality of the pores in the prepared porous carbon matrix can be further guaranteed.
[0029] In some embodiments, mixing the substrate and the porogen in a solvent includes: mixing the substrate and the porogen in the solvent by stirring; optionally, the stirring speed is 100 rpm / min-1500 rpm / min, and more preferably 200 rpm / min-1000 rpm / min.
[0030] In some embodiments, the high-temperature treatment of the first mixture to obtain a porous carbon matrix includes: treating the first mixture at a first temperature to obtain a second mixture, the second mixture being a solid mixture; treating the second mixture at a second temperature to obtain a carbon precursor; and treating the carbon precursor at a third temperature to obtain the porous carbon matrix.
[0031] In the embodiments of this application, a first mixture is first treated at a first temperature, during which excess solvent evaporates and the substrate is initially solidified into a second mixture. Then, the second mixture is treated at a second temperature, during which the first mixture is further solidified to form a carbon precursor. Subsequently, the carbon precursor is treated at a third temperature, during which the porogen and residual solvent in the carbon precursor undergo pyrolysis, generating gas at high temperature to create pores within the substrate. Thus, through the aforementioned multi-temperature, multi-step heating process, the first mixture can be transformed into a porous carbon matrix with an internally cross-linked pore structure. By employing multi-temperature, multi-step heating, the uniformity of the porogen's distribution in the carbon precursor can be effectively improved, resulting in a uniform distribution of pores within the final porous carbon matrix.
[0032] In some embodiments, the first temperature, the second temperature, and the third temperature satisfy one or more of the following (I)-(III): (I) the first temperature is 40℃-80℃, optionally 40℃-60℃; (II) the second temperature is 100℃-200℃, optionally 150℃-180℃; (III) the third temperature is 600℃-1200℃, optionally 800℃-1000℃.
[0033] In the embodiments of this application, by controlling the first temperature within a suitable range, it is possible to avoid situations where the first temperature is too high, resulting in a large number of micropores accumulating locally, and ultimately the resulting channel length is too long or the channel size is too large; or to avoid situations where the first temperature is too low, which is not conducive to the solidification and molding of the first mixture and affects subsequent processing.
[0034] In some embodiments, the preparation method includes: crushing the second mixture before treating the second mixture at the second temperature.
[0035] In some embodiments, the preparation method further includes: crushing the carbon precursor before treating it at the third temperature; optionally, the particle size of the carbon precursor after crushing is 1μm-1000μm, more preferably 5μm-100μm.
[0036] In some embodiments, treating the carbon precursor at a third temperature includes treating the carbon precursor in an inert gas at the third temperature; optionally, the inert gas includes at least one of nitrogen, argon, and helium.
[0037] In some embodiments, the preparation method further includes: before depositing the silicon-based particles in the porous carbon matrix, performing impurity removal and / or demagnetization treatment on the porous carbon matrix.
[0038] In some embodiments, the atmosphere for chemical vapor deposition is a mixture of silane gas and hydrogen gas; optionally, the volume of the silane gas accounts for 10%-50% of the volume of the mixture gas.
[0039] In some embodiments, the flow rate of the silane gas in the chemical vapor deposition is 0.5 L / min to 1 L / min; and / or, the temperature of the chemical vapor deposition is 500°C to 800°C.
[0040] In the embodiments of this application, by controlling the conditions of chemical vapor deposition to meet the above conditions, it is beneficial for silane gas to slowly enter the interior of the porous carbon matrix and decompose and deposit uniformly in the pores of the porous carbon matrix, thereby avoiding the deposition of silicon-based particles on the material surface and helping to reduce the resistivity of silicon-carbon composite materials.
[0041] Thirdly, a secondary battery is provided, including a negative electrode sheet, said negative electrode sheet comprising a silicon-carbon composite material as described in any embodiment of the first aspect, or comprising a silicon-carbon composite material prepared according to the method described in any embodiment of the second aspect.
[0042] Fourthly, an electrical device is provided, the electrical device comprising the secondary battery in any embodiment of the third aspect. Attached Figure Description
[0043] To more clearly illustrate the technical solutions of the embodiments of this application, the drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort. In the drawings, the drawings are not drawn to scale.
[0044] Figure 1 This is a scanning electron microscope image of a porous carbon matrix according to an embodiment of this application.
[0045] Figure 2 This is another scanning electron microscope image of a porous carbon matrix according to an embodiment of this application.
[0046] Figure 3 This is a scanning electron microscope image of a silicon-carbon composite material according to an embodiment of this application.
[0047] Figure 4 This is another scanning electron microscope image of a silicon-carbon composite material according to an embodiment of this application.
[0048] Figure 5 This is an X-ray diffraction peak pattern of a silicon-carbon composite material according to an embodiment of this application.
[0049] Figure 6 This is a schematic flowchart illustrating a method for preparing a silicon-carbon composite material according to an embodiment of this application.
[0050] Figure 7 This is another illustrative flowchart of a method for preparing a silicon-carbon composite material according to an embodiment of this application.
[0051] Figure 8 This is a schematic structural diagram of a secondary battery according to an embodiment of this application.
[0052] Figure 9 This is a schematic structural diagram of a battery module according to an embodiment of this application.
[0053] Figure 10 This is a schematic structural diagram of a battery pack according to an embodiment of this application.
[0054] Figure 11 This is another schematic structural diagram of a battery pack according to an embodiment of this application.
[0055] Figure 12 This is a schematic structural diagram of an electrical device according to an embodiment of this application. Detailed Implementation
[0056] The following detailed description, with appropriate reference to the accompanying drawings, discloses embodiments of the silicon-carbon composite material, a method for preparing the silicon-carbon material, a negative electrode sheet containing the silicon-carbon material, a secondary battery, a battery module, a battery pack, an electrical device, and the application of the silicon-carbon material in the preparation of a secondary battery. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0057] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0058] In the description of this application, it should be noted that, unless otherwise stated, "a plurality of" means two or more; the terms "upper," "lower," "left," "right," "inner," and "outer," etc., indicating orientation or positional relationships, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation on this application. Furthermore, the terms "first," "second," and "third," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance. "Vertical" is not vertical in the strict sense, but within the allowable tolerance range. "Parallel" is not parallel in the strict sense, but within the allowable tolerance range.
[0059] The directional terms used in the following description refer to the directions shown in the figures and are not intended to limit the specific structure of this application. It should also be noted in the description of this application that, unless otherwise explicitly specified and limited, the terms "installation," "connection," and "joining" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium. Those skilled in the art can understand the specific meaning of the above terms in this application based on the specific circumstances.
[0060] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0061] Unless otherwise specified, the term "or" is inclusive in this application. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0062] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0063] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0064] Typically, a secondary battery consists of a positive electrode, a negative electrode, an electrolyte, and a separator. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and releasing. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, primarily prevents short circuits while allowing ions to pass through.
[0065] Secondary batteries can include lithium-ion batteries, sodium-ion batteries, magnesium-ion batteries, etc. This application uses a lithium-ion battery as an example. A lithium-ion battery is a typical secondary battery. Because it relies on the chemical reaction of lithium ions being inserted and extracted between the positive and negative electrodes for charging and discharging, a lithium-ion battery is also known as a rocking chair battery. During the charging process of a lithium-ion battery, lithium ions are extracted from the positive electrode, move, and insert into the negative electrode; while during the discharging process, lithium ions are extracted from the negative electrode, move, and insert into the positive electrode.
[0066] In recent years, secondary batteries have seen tremendous development and have been widely used in many fields such as power tools, electronic products, electric vehicles, and aerospace. At the same time, higher requirements have been placed on the volume capacity, energy density, and cycle performance of secondary batteries.
[0067] For anode materials, graphite is one of the most commonly used due to its wide availability, abundant reserves, and stable electrochemical properties. However, graphite's theoretical capacity (372 mA·h / g) is relatively low, which can no longer meet the demands for higher volumetric capacity and energy density in rechargeable batteries. Silicon, on the other hand, also has wide availability and abundant reserves, and possesses extremely high theoretical capacity (4200 mAh / g) and low lithium intercalation potential. Furthermore, it exhibits good chemical stability in electrolytes and is less prone to side reactions with the electrolyte, thus gradually becoming a more ideal anode material for rechargeable batteries.
[0068] In the electrochemical reactions of secondary batteries using silicon as the anode material, on the one hand, due to the difference in crystal structure between silicon and graphite, silicon undergoes tremendous volume expansion during lithium-ion insertion, with an expansion rate reaching 300%. This expansion easily damages the structure of the anode material, causing surface breakage or detachment from the current collector. Furthermore, in secondary batteries using silicon as the anode material, an SEI (Solid Electrolyte Interphase) film forms on the surface of the anode material. As the silicon expands, the surface of the anode material is continuously damaged, and the SEI film is constantly destroyed and regenerated, resulting in unnecessary lithium-ion consumption and affecting the capacity of the secondary battery. On the other hand, silicon is a semiconductor material with low conductivity and high interfacial impedance, which greatly hinders electron conduction on and within the silicon surface, affecting the rate performance of the secondary battery.
[0069] In view of this, this application provides a silicon-carbon composite material comprising a porous carbon matrix and silicon-based particles distributed within the porous carbon matrix. The silicon-based particles are distributed within the interlinked pores of the porous carbon matrix, giving the silicon-carbon composite material extremely high volumetric capacity and energy density. The porous carbon matrix has a three-dimensional network structure, exhibiting good electrical conductivity, while the spaces within its interlinked pores can accommodate and restrict the volume expansion of the silicon-based particles, resulting in excellent electrical conductivity, rate performance, and cycle life of the silicon-carbon composite material.
[0070] It should be understood that the “lithium intercalation” or “intercalation” process described in this application refers to the process in which lithium ions are intercalated into the positive electrode material and the negative electrode material due to an electrochemical reaction, while the “deintercalation”, “delithiation”, or “deintercalation” process described in this application refers to the process in which lithium ions are deintercalated into the positive electrode material and the negative electrode material due to an electrochemical reaction.
[0071] First, this application provides a silicon-carbon composite material comprising a porous carbon matrix and silicon-based particles. The porous carbon matrix contains multiple channels with a width of 5 nm to 50 nm, and the silicon-based particles are distributed within the channels. Furthermore, the porous carbon matrix satisfies the following condition: 1.0 ≤ V 总 / S 总≤10, unit: 10 -7 cm; where S 总 This refers to the total surface area occupied by channels with widths ranging from 5nm to 50nm, measured in units of ×10⁻¹⁰. 4 cm 2 / g;V 总 The total pore volume occupied by channels with a width of 5nm-50nm, measured in cm. 3 / g.
[0072] Specifically, V 总 / S 总 It can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or its value can be within the range obtained by any combination of the above two values.
[0073] Figure 1 and Figure 2 This is a scanning electron microscope (SEM) image of a porous carbon matrix according to an embodiment of this application. (Reference) Figure 1 and Figure 2 The porous carbon matrix has abundant pore structures and a three-dimensional network of cross-linked carbon skeletons.
[0074] V 总 / S 总 This represents the average pore length of the channels in the porous carbon matrix. Due to its multiple channel structures, the porous carbon matrix forms a three-dimensional network carbon framework. This carbon framework acts as an electronic conductor, and its conductivity model can be compared to that of a parallel circuit. Ohm's law for a parallel circuit satisfies equation (I): 1 / R 总 = 1 / R1 + 1 / R2 + 1 / R3 + ... + 1 / R m Formula (I) Among them, R 总 R is the total resistance of the parallel circuit, R1 is the resistance of the first parallel branch, R2 is the resistance of the second parallel branch, R3 is the resistance of the third parallel branch, and R... m Let be the resistance of the m-th parallel branch, where m is an integer and m≥2. Therefore, for this porous carbon matrix, controlling its unit pore length within a small range allows for more parallel carbon skeleton branches in the porous carbon matrix, resulting in lower resistivity.
[0075] Figure 3 and Figure 4 Scanning electron microscopy (SEM) images of the silicon-carbon composite material provided in the embodiments of this application. See also... Figures 1 to 4The silicon-carbon composite material provided in this application mainly consists of a porous carbon matrix and silicon-based particles distributed within the pore structure of the porous carbon matrix. The porous carbon matrix, unlike ordinary carbon matrices, possesses multiple pore structures, at least two of which are interconnected, forming a three-dimensional network structure. This porous carbon matrix exhibits good electrical conductivity, effectively improving the electron transport efficiency at the silicon-carbon interface after silicon-based particles are composited onto it. Furthermore, its abundant cross-linked pore structure effectively accommodates and restricts the volume expansion of silicon-based particles during battery cycling, thereby effectively improving the structural stability of the silicon-carbon composite material and reducing structural damage caused by the volume expansion of silicon-based particles. Figure 3 and Figure 4 In the silicon-carbon composite material shown, silicon-based particles are uniformly distributed within the porous structure. Therefore, when this silicon-carbon composite material is applied to the negative electrode of a battery, it can effectively improve the battery's volumetric capacity and energy density, and exhibit good cycle performance and rate performance.
[0076] Alternatively, in some embodiments, 1.0 ≤ V 总 / S 总 ≤10, optionally, 2≤V 总 / S 总 ≤5, unit: ×10 -7 cm.
[0077] Specifically, V 总 / S 总 It can be 2, 2.5, 3, 3.5, 4, 4.5, 5, or its value is within the range obtained by any combination of the above two values.
[0078] In this embodiment, by further reducing the length range of the pores in the porous carbon matrix, the conductivity of the porous carbon matrix can be further improved, thereby enhancing the conductivity of the silicon-carbon composite material and helping to improve the cycle stability and rate performance of the battery.
[0079] Alternatively, in some embodiments, 1≤S 总 ≤50, optionally, 1≤S 总 ≤30, unit: ×10 4 m 2 / g.
[0080] Specifically, S 总 It can be 1, 3, 4, 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32, 34, 36, 38, 40, 42, 44, 46, 48, 50, or its value range is within the range obtained by any two of the above value combinations.
[0081] Alternatively, in some embodiments, 0.002 ≤ V 总 ≤0.250, optionally, 0.004≤V 总 ≤0.200, unit: cm 3 / g.
[0082] Specifically, V 总 It can be 0.002, 0.004, 0.007, 0.008, 0.009, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.18, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, or a combination of these values within the range obtained by any two combinations of the above values.
[0083] In this embodiment, the porous carbon matrix that meets the above conditions has a three-dimensional cross-linked network structure and a large specific surface area, providing sufficient space on the surface of the porous carbon matrix for the distribution of silicon-based particles. Therefore, the silicon-carbon composite material obtained by combining the porous carbon matrix and silicon-based particles possesses extremely high volumetric capacity and energy density. Simultaneously, the pores in the porous carbon matrix that meets the above conditions also have sufficient volume to accommodate and limit the expansion of the silicon-based particles composited within the pores during battery cycling, thereby maintaining the structural stability of the silicon-carbon composite material during battery cycling and effectively improving the battery's cycle performance.
[0084] Optionally, in some embodiments, the grain size of the silicon-based particles is less than or equal to 20 nm, preferably 2 nm to 10 nm.
[0085] Optionally, in some embodiments, the volumetric particle size distribution D of the porous carbon matrix is... v50 ≤10μm, optionally 5≤D v50 ≤10μm; and / or the volumetric particle size distribution D of the porous carbon matrix v90 ≤20μm, optionally 10≤D v90 ≤15μm.
[0086] Specifically, the porous carbon matrix undergoes a crushing process before being combined with silicon-based particles to form a silicon-carbon composite material, resulting in a granular porous carbon matrix. Combining the micron-sized porous carbon matrix with silicon-based particles facilitates the entry and deposition of silicon-based particles into the pores of the porous carbon matrix, rather than depositing them on the surface of the carbon skeleton. If silicon-based particles are deposited only on the surface, the highly conductive porous carbon matrix will be encapsulated by the less conductive silicon-based particles, compromising the overall conductivity of the silicon-carbon composite material. Therefore, crushing the porous carbon matrix before composite formation helps to ensure uniform deposition of silicon-based particles within the pores, thus improving the conductivity of the silicon-carbon composite material.
[0087] Optionally, in some embodiments, the content of silicon-based particles in the silicon-carbon composite material is 25%-65%, and optionally 35%-45%.
[0088] Specifically, the content of silicon-based particles in silicon-carbon composite materials can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, or 45%, or a value within the range obtained by any combination of the above two values.
[0089] In this embodiment, by controlling the content of silicon-based particles in the silicon-carbon composite material within a suitable range, on the one hand, sufficient silicon-based particles can be incorporated into the silicon-carbon composite material, maximizing its volumetric capacity and energy density; on the other hand, since silicon-based particles have poor conductivity, controlling their content within a suitable range also avoids excessive silicon-based particles in the silicon-carbon composite material, which could negatively impact its conductivity. Therefore, by controlling the content of silicon-based particles in the silicon-carbon composite material, the silicon-carbon composite material can possess both high specific capacity and good conductivity.
[0090] Optionally, in some embodiments, the powder resistivity of the porous carbon matrix at a pressure of 4 MPa is 1 Ω / cm-300 Ω / cm, and optionally 1 Ω / cm-100 Ω / cm.
[0091] Specifically, the resistivity of the porous carbon matrix powder under a pressure of 4 MPa can be 1 Ω / cm, 5 Ω / cm, 10 Ω / cm, 15 Ω / cm, 20 Ω / cm, 25 Ω / cm, 30 Ω / cm, 35 Ω / cm, 40 Ω / cm, 45 Ω / cm, 50 Ω / cm, 55 Ω / cm, 60 Ω / cm, 65 Ω / cm, 70 Ω / cm, 75 Ω / cm, 80 Ω / cm, 85 Ω / cm, 90 Ω / cm, 95 Ω / cm, 100 Ω / cm, 150 Ω / cm, 200 Ω / cm, 250 Ω / cm, 300 Ω / cm, or a value within the range obtained by any combination of the above two values.
[0092] In this embodiment, the porous carbon scaffold itself has a low resistivity due to its cross-linked network structure. After being combined with silicon-based particles, the silicon-carbon composite material also has a low resistivity, exhibiting good conductivity when used as an electrode active material, which helps to improve the cycle stability of the battery.
[0093] In some embodiments, the powder resistivity of the silicon-carbon composite material at 12 MPa pressure is R ≤ 300 Ω / cm, optionally 1 Ω / cm-200 Ω / cm; and / or the powder resistivity of the silicon-carbon composite material at 16 MPa pressure is R ≤ 200 Ω / cm, optionally 1 Ω / cm-100 Ω / cm.
[0094] Specifically, the resistivity of silicon-carbon composite material powder under 12MPa pressure can be 1Ω / cm, 5Ω / cm, 10Ω / cm, 15Ω / cm, 20Ω / cm, 25Ω / cm, 30Ω / cm, 35Ω / cm, 40Ω / cm, 45Ω / cm, 50Ω / cm, 55Ω / cm, 60Ω / cm, 65Ω / cm, 70Ω / cm, 75Ω / cm, 80Ω / cm, 85Ω / cm, 90Ω / cm, 95Ω / cm, 100Ω / cm, 150Ω / cm, 200Ω / cm, 250Ω / cm, 300Ω / cm, or a value within the range obtained by any combination of the above two values. The resistivity of silicon-carbon composite powder under 16MPa pressure can be 1Ω / cm, 5Ω / cm, 10Ω / cm, 15Ω / cm, 20Ω / cm, 25Ω / cm, 30Ω / cm, 35Ω / cm, 40Ω / cm, 45Ω / cm, 50Ω / cm, 55Ω / cm, 60Ω / cm, 65Ω / cm, 70Ω / cm, 75Ω / cm, 80Ω / cm, 85Ω / cm, 90Ω / cm, 95Ω / cm, 100Ω / cm, 150Ω / cm, or 200Ω / cm, or a value within the range obtained by any combination of the above two values.
[0095] Optionally, in some embodiments, the silicon-carbon composite material satisfies one or more of the following (1)-(6):
[0096] (1) The volumetric particle size distribution of silicon-carbon composite material is Dv10≤5μm, which can optionally be 3≤Dv10≤5μm.
[0097] (2) The volumetric particle size distribution of silicon-carbon composite material is Dv50≤10μm, which can optionally be 5≤Dv50≤10μm.
[0098] (3) The volumetric particle size distribution of silicon-carbon composite material is Dv90≤20μm, which can optionally be 10≤Dv50≤15μm.
[0099] (4) The particle size distribution of silicon-carbon composite material satisfies: (Dv90-Dv10) / Dv50≤1.8, and optionally, 1.5≤(Dv90-Dv10) / Dv50≤1.7.
[0100] (5) The compaction density of the silicon-carbon composite material at 2 MPa pressure is 1 g / cm³.3 -1.5g / cm 3 Optionally, it can be 1.1 g / cm³. 3 -1.3g / cm 3 .
[0101] (6) The specific surface area (SSA) of the silicon-carbon composite material is 2m². 2 / g-10m 2 / g, optionally 3m 2 / g-7m 2 / g.
[0102] Specifically, the silicon-carbon composite material obtained by combining a porous carbon matrix and silicon-based particles has at least one of the properties mentioned in (1)-(6).
[0103] For example, the compaction density of silicon-carbon composite materials under 2 MPa pressure can be 1 g / cm³. 3 1.1g / cm 3 1.2g / cm 3 1.3g / cm 3 1.4g / cm 3 1.5g / cm 3 , or its value is within the range obtained by combining any two of the above values.
[0104] For example, the SSA of silicon-carbon composites can be 2m. 2 / g, 2.5m 2 / g、3m 2 / g, 3.5m 2 / g、4m 2 / g, 4.5m 2 / g、5m 2 / g, 5.5m 2 / g、6m 2 / g, 6.5m 2 / g、7m 2 / g, 7.5m 2 / g、8m 2 / g, 8.5m 2 / g、9m 2 / g, 9.5m 2 / g, 10m 2 / g.
[0105] Optionally, in some embodiments, the peak value of the X-ray diffraction (XRD) peak of the silicon-carbon composite material between a diffraction angle of 28°-29° is denoted as P1, and the peak value of the XRD peak of the silicon-based particles between a diffraction angle of 42°-45° is denoted as P2, then 2≤P1 / P2≤4; optionally, 600≤P1≤800; optionally, 200≤P2≤400.
[0106] Figure 5 The XRD peak diagram of a silicon-carbon composite material in an embodiment of this application is shown.
[0107] like Figure 5 As shown, the silicon-carbon composite material has obvious diffraction peaks in the diffraction angle range of 28°-29° and 42°-45°, with the diffraction angle of 28°-29° being the characteristic peak of carbon material and the diffraction angle of 42°-45° being the characteristic peak of silicon material.
[0108] In order to obtain the above-mentioned silicon-carbon composite material, this application also provides a method for preparing the silicon-carbon composite material. Figure 6 This is a schematic flowchart illustrating a method for preparing a silicon-carbon composite material according to an embodiment of this application.
[0109] like Figure 6 As shown, the preparation method 600 of silicon-carbon composite material includes:
[0110] S601, the substrate and the pore-forming agent are mixed in a solvent to obtain a first mixture;
[0111] S602, high-temperature treatment of the first mixture to obtain a porous carbon matrix;
[0112] S603, a silicon-carbon composite material is obtained by depositing silane gas onto a porous carbon matrix through chemical vapor deposition (CVD).
[0113] Optionally, the silicon-based particles include at least one of silicon oxide compounds, nano-silicon, and alloy silicon. Silicon oxide compounds include, but are not limited to, silicon monoxide and silicon dioxide; alloy silicon includes, but is not limited to, silicone alloys, ferrosilicon alloys, and aluminum-silicon alloys.
[0114] Optionally, the substrate includes at least one of resin, sugar, or other polymers. Optionally, the resin includes, but is not limited to, linear phenolic resin, soluble phenolic resin, epoxy resin, and polyurethane; optional, the sugar includes, but is not limited to, glucose, sucrose, fructose, starch, amylopectin, amylose, lignin, dextrin, and maltodextrin; optional, other polymers include, but are not limited to, acrylates, styrene polymers, urethane, rubber, and nylon.
[0115] Optionally, the pore-forming agent includes at least one of sodium chloride, potassium chloride, zinc chloride, sodium carbonate, potassium carbonate, and zinc carbonate.
[0116] Optionally, the solvent may include, but is not limited to, water or alcohol. For example, the solvent may also be a mixture of water and alcohol, i.e., an alcohol solution. Alcohols include, but are not limited to, methanol, ethanol, ethylene glycol, polyethylene glycol, glycerol, isopropanol, or polyols.
[0117] Optionally, in S601, the mass ratio of the substrate to the pore-forming agent is 1:5-10:1, and optionally 2:1-5:1.
[0118] Specifically, the mass ratio of the substrate to the pore-forming agent can be 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, or the ratio can be within the range obtained from any two of the above values.
[0119] In this embodiment, the amount of porogen can be determined based on the amount of substrate, ensuring that the mass ratio of substrate to porogen is within a suitable range. This effectively avoids the situation where insufficient porogen fails to generate enough gas to form elongated channels, while also preventing the situation where excessive porogen leads to intense local reactions, rapidly generating large amounts of gas and creating large pores or voids. In other words, by controlling the mass ratio of substrate to porogen, the shape and size of the channels in the porous carbon matrix can be effectively controlled, thereby preparing a channel structure of suitable size and elongated shape.
[0120] Optionally, in S601, the mass ratio of the substrate to the solvent is 1:100-10:1, or optionally 1:2-10:1.
[0121] Specifically, the mass ratio of the substrate to the solvent can be 1:100, 1:90, 1:80, 1:70, 1:60, 1:50, 1:40, 1:30, 1:20, 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 5:1, 7:1, 8:1, 9:1, 10:1, or the ratio can be within the range obtained from any two of the above values.
[0122] In this embodiment, the amount of solvent is determined based on the amount of substrate used, ensuring that the mass ratio of substrate to solvent is within a suitable range. This effectively avoids situations where insufficient solvent results in excessively high viscosity of the first mixture, preventing timely dispersion of gas generated by the pore-forming agent and leading to excessively large or long pores. Conversely, it also avoids situations where excessive solvent results in insufficient viscosity of the first mixture, causing rapid gas expulsion and pore-forming failure. In other words, by controlling the mass ratio of substrate to solvent, the viscosity of the first mixture can be effectively regulated, ensuring uniform dispersion of gas generated by the pore-forming agent within the first mixture. This guarantees a uniform pore distribution and appropriate size and shape within the porous carbon matrix.
[0123] Optionally, in S601, mixing the substrate and the porogen in a solvent includes: mixing the substrate and the porogen in the solvent by stirring.
[0124] Specifically, there are various methods for uniformly mixing the substrate, pore-forming agent, and solvent, such as stirring, heating and stirring, high-pressure stirring, etc. Taking stirring as an example, the solvent can be placed in a container equipped with a stirring device such as a stir bar or a spiral stirrer. The stirring device stirs the solvent at a certain speed. During this process, the substrate and pore-forming agent are added to the solvent. After stirring for a certain period of time, a first mixture with a homogeneous bulk phase is obtained. It should be understood that the process of adding the substrate to the solvent can be as follows: the substrate is added first, then the pore-forming agent; or the pore-forming agent is added first, then the substrate; or the substrate and the pore-forming agent can be added simultaneously. The embodiments of this application do not limit this.
[0125] Optionally, the stirring speed is 100 rpm / min-1500 rpm / min, preferably 200 rpm / min-1000 rpm / min.
[0126] Specifically, the stirring speed can be 100 rpm / min, 200 rpm / min, 300 rpm / min, 400 rpm / min, 500 rpm / min, 600 rpm / min, 700 rpm / min, 800 rpm / min, 900 rpm / min, 1000 rpm / min, 1100 rpm / min, 1200 rpm / min, 1300 rpm / min, 1400 rpm / min, 1500 rpm / min, or a value within the range obtained from any two of the above values.
[0127] At the preferred stirring speed described above, the substrate, pore-forming agent, and solvent can be mixed quickly and evenly, while also avoiding waste caused by splashing of liquid mixture due to excessive speed.
[0128] Figure 7This is another schematic flowchart of a method 600 for preparing a silicon-carbon composite material according to an embodiment of this application.
[0129] like Figure 7 As shown, optionally, in S602, high-temperature treatment of the first mixture to obtain a porous carbon matrix includes:
[0130] S6021, the first mixture is treated at a first temperature T1 to obtain a second mixture, the second mixture being a solid mixture.
[0131] S6022, the second mixture is treated at a second temperature T2 to obtain a carbon precursor.
[0132] S6023, a porous carbon matrix is obtained by treating the carbon precursor at a third temperature T3.
[0133] Specifically, in S6021, a large amount of solvent evaporates during this process, and the fluid first mixture is initially solidified at T1, transforming it into a solid second mixture in which the porogen is uniformly dispersed in the matrix. In S6022, the second mixture is treated at T2, further evaporating the solvent and solidifying it into a carbon precursor, which has a more stable structure than the second mixture. In S6023, the carbon precursor is treated at T3, where the porogen decomposes to generate gas, creating pores within the carbon precursor. The carbon precursor at T3 then reacts to form a porous carbon framework, i.e., a porous carbon matrix.
[0134] In this embodiment, the uniformity of the distribution of the pore-forming agent in the carbon precursor can be effectively controlled through a multi-temperature, multi-step heating process, thereby transforming the first mixture into a porous carbon matrix with a uniform cross-linked pore structure inside.
[0135] Optionally, in S6021, T1 is 40℃-80℃, or optionally T1 is 40℃-60℃.
[0136] Specifically, T1 can be 40℃, 45℃, 50℃, 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, or a value within the range obtained from any two of the above values.
[0137] In this embodiment, T1 is the initial curing temperature of the first mixture. By controlling T1 within a suitable range, it is possible to avoid T1 being too high, causing the pore-forming agent to be too dispersed, which would prevent the channels from cross-linking during the subsequent pore-forming process and result in a large number of micron-sized pores or voids. It is also possible to avoid T1 being too low, which would be detrimental to the curing and shaping of the first mixture and affect the subsequent preparation process.
[0138] Optionally, in S6022, T2 is 100℃-200℃, or optionally T2 is 130℃-180℃.
[0139] Specifically, T2 can be 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, or a value within the range obtained from any two of the above values.
[0140] Optionally, in S6023, T3 is 600℃-1200℃, or optionally T3 is 800℃-1000℃.
[0141] Specifically, T3 can be 600℃, 700℃, 800℃, 900℃, 1000℃, 1100℃, 1200℃, or a value within the range obtained from any two of the above values.
[0142] Optionally, prior to S6022, preparation method 600 further includes crushing the second mixture.
[0143] Specifically, after the first mixture has initially solidified into the second mixture, the second mixture can be processed into a powdered solid through coarse crushing, fine crushing, and grinding processes, i.e., the second mixture is subjected to crushing treatment. Treating the second mixture with T2 after crushing helps to prevent the solvent inside the lumpy second mixture from failing to evaporate or further solidify.
[0144] Optionally, before S6023, preparation method 600 further includes crushing the carbon precursor. Optionally, the particle size of the carbon precursor after crushing is 1μm-1000μm, or optionally 5μm-100μm.
[0145] Specifically, after obtaining the carbon precursor, it can be further crushed into micron-sized particles. Then, treatment with T3 helps to increase the degree of carbonization reaction and avoids the situation where large granular carbon precursors only have surface carbonization without internal carbonization. This improves the quality of the prepared porous carbon matrix. The particle size of the crushed carbon precursor can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 50 μm, 100 μm, 150 μm, 200 μm, 300 μm, 400 μm, 500 μm, 600 μm, 700 μm, 800 μm, 900 μm, 1000 μm, or a value within the range obtained from any two of the above values.
[0146] Optionally, in S6023, treating the carbon precursor with T3 includes treating the carbon precursor with T3 in an inert gas. Optionally, the inert gas includes at least one of nitrogen (N2), argon (Ar), and helium (He).
[0147] Specifically, high-temperature treatment of carbon precursors in an inert gas environment can protect them from reaction with oxygen, allowing them to undergo carbonization and thus obtain a porous carbon matrix with abundant pore structures.
[0148] Optionally, prior to S6023, preparation method 600 further includes impurity removal and / or demagnetization treatment of the porous carbon matrix. Through impurity removal, demagnetization, and other processes, the carbon precursor is further screened to obtain more suitable micron-sized carbon precursor particles, which helps improve the quality of the prepared porous carbon matrix.
[0149] Optionally, in S604, the CVD process typically places the porous carbon matrix in a silicon-containing gas at a high temperature, allowing silicon in the silicon-containing gas to deposit within the pores of the porous carbon to generate silicon-based particles. The silicon-containing gas includes at least one of silane gas, silicon dichloride, silicon trichloride, and silicon tetrachloride. The silicon-containing gas may also include other gases such as hydrogen and inert gases. In cases where the silicon-containing gas includes multiple gases, taking silicon dichloride and nitrogen as an example, the silicon-containing gas may include 0.1%-1% silicon dichloride and the remainder nitrogen by volume, or it may include 1%-10% silicon dichloride and the remainder nitrogen by volume, or it may include 10%-50% silicon dichloride and the remainder nitrogen by volume, or it may include more than 50% silicon dichloride and the remainder nitrogen by volume.
[0150] Preferably, the CVD atmosphere is a mixture of silane and hydrogen gas. Optionally, the volume of silane gas accounts for 10%-50% of the volume of the mixture.
[0151] Optionally, the CVD temperature is 500℃-800℃. Specifically, the CVD temperature can be 500℃, 550℃, 600℃, 650℃, 700℃, 750℃, 800℃, or a value within the range obtained from any two of the above values.
[0152] Optionally, the flow rate of the CVD silane gas is 0.5 L / min to 1 L / min. Specifically, the flow rate of the silicon-containing material can be 0.5 L / min, 0.55 L / min, 0.6 L / min, 0.65 L / min, 0.7 L / min, 0.75 L / min, 0.8 L / min, 0.85 L / min, 0.9 L / min, 0.95 L / min, or 1 L / min, or a value within the range obtained from any two of the above values.
[0153] In this embodiment, a silicon-carbon composite material is obtained by combining a porous carbon matrix and silicon-based particles through CVD. By controlling the CVD to meet the above conditions, it is beneficial for silicon in the silicon-containing gas to be uniformly deposited in the pores of the porous carbon matrix, thereby obtaining a silicon-carbon composite material with excellent electrical conductivity.
[0154] Alternatively, in some other embodiments, porous carbon matrix and silicon-based particles can be composited by plasma-enhanced chemical vapor deposition (PECVD).
[0155] In this embodiment, preparation method 600 first involves uniformly dispersing the substrate and pore-forming agent in a solvent. During subsequent high-temperature treatment, the solvent and pore-forming agent work together to create pores, resulting in elongated and cross-linked channels. The carbon skeleton containing this special channel structure exhibits a three-dimensional network structure, giving the porous carbon matrix a low resistivity. During the chemical vapor deposition of the composite silicon-based particles and the multi-layered carbon matrix, the flow rate of silane gas is controlled within a suitable range, allowing the silane gas to slowly and fully penetrate the pores of the porous carbon matrix and uniformly decompose and deposit within the channels, preventing silicon-based particles from depositing only on the material surface. Consequently, the silicon-carbon interface extends fully into the interior of the silicon-carbon composite material, significantly improving the material's conductivity compared to ordinary silicon-carbon materials. The resistivity of the silicon-carbon composite material prepared by the above method 600 is typically 100 Ω / cm to 10000 Ω / cm.
[0156] This application also provides a negative electrode sheet, a secondary battery, a battery module, a battery pack, and an electrical device. The negative electrode sheet, secondary battery, battery module, battery pack, and electrical device of this application will now be described with appropriate reference to the accompanying drawings.
[0157] [Negative electrode plate]
[0158] A negative electrode typically includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0159] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0160] In one embodiment, the negative electrode active material is a silicon-carbon composite material provided in any embodiment of this application.
[0161] Optionally, in one embodiment, the negative electrode active material may also include a mixture of at least one other negative electrode active material known in the art for use in batteries and the silicon-carbon composite material provided in any embodiment of this application. As an example, other negative electrode active materials may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, elemental silicon, silicon oxide compounds, silicon-carbon composite materials, silicon-nitrogen composites, silicon alloys, tin-based materials, and lithium titanate. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys.
[0162] Optionally, in one embodiment, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0163] Optionally, in one embodiment, the negative electrode film layer includes an adhesive. The adhesive may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0164] Optionally, in one embodiment, the negative electrode film layer includes a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0165] Optionally, in one embodiment, the negative electrode film layer also includes other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0166] Optionally, in one embodiment, the negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto a negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0167] [Positive electrode plate]
[0168] The positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector, the positive electrode film layer including the positive electrode active material of the first aspect of this application.
[0169] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0170] Optionally, in one embodiment, the positive electrode active material may be a known positive electrode active material for batteries. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM523), LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM211), LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM811), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.
[0171] In some embodiments, the positive electrode film layer may optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0172] Optionally, in one embodiment, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0173] Optionally, in one embodiment, the positive electrode film layer further includes a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0174] Optionally, in one embodiment, the positive electrode material may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0175] Optionally, in one embodiment, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0176] [Electrolytes]
[0177] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0178] Optionally, in one embodiment, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0179] Optionally, in one embodiment, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0180] Optionally, in one embodiment, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0181] Optionally, in one embodiment, the electrolyte further includes additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0182] [Isolation Component]
[0183] Optionally, in one embodiment, the secondary battery further includes a separator. This application does not impose any particular limitation on the type of separator; for example, any known porous membrane with good chemical and mechanical stability can be selected.
[0184] Optionally, in one embodiment, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0185] Optionally, in one embodiment, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding process or a stacking process.
[0186] Optionally, in one embodiment, the secondary battery may include an outer packaging. This outer packaging can be used to encapsulate the electrode assembly and electrolyte described above.
[0187] Optionally, in one embodiment, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft pack, such as a pouch-type soft pack. The material of the soft pack can be plastic; examples of plastics include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0188] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 8 This is an example of a square-structured secondary battery, 800.
[0189] Optionally, in one embodiment, reference is made to Figure 8 The secondary battery 800's outer packaging includes a casing 801 and a cover plate 802. The casing 801 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The casing 801 has an opening communicating with the receiving cavity, and the cover plate 802 can close the opening to seal the receiving cavity. A positive electrode sheet, a negative electrode sheet, and a separator are formed into an electrode assembly 803 through a winding or stacking process. The electrode assembly 803 is encapsulated within the receiving cavity and immersed in the electrode assembly 803. The secondary battery 800 may contain one or more electrode assemblies 803. Those skilled in the art can select according to actual needs.
[0190] Optionally, in one embodiment, the secondary battery 800 can be assembled into a battery module. The number of secondary batteries 800 contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application scenario and capacity of the battery module.
[0191] Figure 9 This is a schematic structural diagram of battery module 900. (Refer to...) Figure 9 In the battery module 900, multiple secondary batteries 800 can be arranged sequentially along the length of the battery module 900. Of course, they can also be arranged in any other manner. Furthermore, the multiple secondary batteries 800 can be secured with fasteners.
[0192] Alternatively, in one embodiment, the battery module 900 may further include a housing with a receiving space in which a plurality of secondary batteries 800 are received.
[0193] Optionally, in one embodiment, the battery module 900 can also be assembled into a battery pack. The number of battery modules 900 contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application scenario and capacity of the battery pack.
[0194] Figure 10 and Figure 11 This is a schematic diagram of the 1000 battery pack. Please refer to it. Figure 10 and Figure 11 The battery pack 1000 may include a battery box and multiple battery modules 900 disposed within the battery box. The battery box includes an upper box 1001 and a lower box 1002, with the upper box 1001 covering the lower box 1002 to form a closed space for accommodating the battery modules 900. The multiple battery modules 900 can be arranged in any manner within the battery box.
[0195] Figure 12 A schematic diagram of an electrical device 1200 provided in this application.
[0196] It should be understood that the electrical device 1200 includes at least one of the secondary battery 800, battery module 900, or battery pack 1000 provided in this application. The secondary battery 800, battery module 900, or battery pack 1000 can be powered by the electrical device 1200 or can be powered by the energy storage unit of the electrical device 1200. The electrical device 1200 may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0197] As an electrical device 1200, a secondary battery 800, a battery module 900, or a battery pack 1000 can be selected according to its usage requirements.
[0198] As an example, electrical appliance 1200, such as Figure 12 As shown, the electrical device 1200 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the high power and high energy density requirements of the secondary battery 10 of the electrical device 1200, a battery pack 1000 or a battery module 900 can be used.
[0199] As another example, the power-consuming device 1200 could be a mobile phone, tablet computer, laptop computer, etc. This device typically requires a slim and lightweight design and can use a rechargeable battery 800 as its power source.
[0200] In addition, this application also provides an example of the use of silicon-carbon compounds in the preparation of secondary batteries.
[0201] Example
[0202] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0203] Preparation of silicon carbide
[0204] II. Preparation of Porous Carbon Matrix
[0205] Porous carbon matrix 1
[0206] First, 50g of resin with a solid content of 80% was weighed as the base material and 100g of anhydrous ethanol was weighed as the solvent. The anhydrous ethanol was slowly poured into the resin and stirred for a period of time until a homogeneous alcohol solution was obtained. Then, 50g of zinc chloride was weighed as a pore-forming agent and added to the alcohol solution. The mixture was then stirred continuously at 1000 r / min for 3 hours to obtain a homogeneous and clear blended resin solution, i.e., the first mixture. The first mixture was then transferred to a heat-resistant mold and placed in a forced-air drying oven. The first mixture was treated at T1 = 40℃ to allow it to initially solidify, resulting in the second mixture. The second mixture was then coarsely crushed and heat-treated at T2 = 130℃ under oxygen for 10 hours to obtain a carbon precursor. The carbon precursor was then further finely crushed, and the smaller particles were carbonized in a heating device at T3 = 1000℃ under nitrogen for 2 hours to obtain a carbonized product. Finally, the carbonized product was purified, demagnetized, and sieved to obtain a porous carbon matrix 1. Among them, porous carbon matrix 1 satisfies: V 总 =0.068cm 3 S 总 =19.8m 2 V 总 / S 总 =3.43nm.
[0207] Porous carbon matrix 2
[0208] Compared with porous carbon matrix 1, the difference between porous carbon matrix 2 and porous carbon matrix 1 is that the amount of zinc chloride used is 25g and T1 = 60℃.
[0209] Porous carbon matrix 3
[0210] Compared with porous carbon matrix 1, the difference between porous carbon matrix 3 and porous carbon matrix 1 is that the amount of zinc chloride used is 16.67g and the amount of anhydrous ethanol used is 200g.
[0211] Porous carbon matrix 4
[0212] Compared with porous carbon matrix 1, porous carbon matrix 4 differs from porous carbon matrix 1 in that the amount of zinc chloride used is 10g, the amount of anhydrous ethanol used is 500g, T1 = 60℃, and T2 = 150℃.
[0213] Porous carbon matrix 5
[0214] Compared with porous carbon matrix 1, porous carbon matrix 5 differs from porous carbon matrix 1 in that the amount of zinc chloride used is 1.25g, the amount of anhydrous ethanol used is 2000g, T1 = 80℃, and T2 = 150℃.
[0215] Porous carbon matrix 6
[0216] Compared with porous carbon matrix 1, porous carbon matrix 6 differs from porous carbon matrix 1 in that the amount of zinc chloride used is 0.83g, the amount of anhydrous ethanol used is 3000g, T1=80℃, T2=180℃, and T3=800℃.
[0217] Porous carbon matrix 7
[0218] Compared with porous carbon matrix 1, the difference between porous carbon matrix 7 and porous carbon matrix 1 is that the amount of anhydrous ethanol used is 5000g and T1 = 80℃.
[0219] Porous carbon matrix 8
[0220] Compared with porous carbon matrix 1, porous carbon matrix 8 differs from porous carbon matrix 1 in that the amount of zinc chloride used is 5000g, the amount of anhydrous ethanol used is 5000g, T1 = 80℃, T2 = 150℃, and T3 = 800℃.
[0221] Porous carbon matrix 9
[0222] Compared with porous carbon matrix 1, the difference between porous carbon matrix 9 and porous carbon matrix 1 is that the amount of anhydrous ethanol used is 4000g, T1=80℃, T2=180℃, and T3=800℃.
[0223] carbon matrix 1
[0224] Compared with porous carbon matrix 1, the difference between carbon matrix 1 and porous carbon matrix 1 is that T1 = 120℃ and T2 = 250℃.
[0225] carbon matrix 2
[0226] Compared with porous carbon matrix 1, carbon matrix 2 differs from porous carbon matrix 1 in that the amount of zinc chloride used is 0.5g, the amount of anhydrous ethanol is 4000g, T1 = 120℃, T2 = 250℃, and the second mixture is heated under a nitrogen atmosphere.
[0227] Heating equipment includes, but is not limited to, atmosphere box furnaces, tube furnaces, rotary kilns, and pusher kilns.
[0228] Preparation of I-II silicon carbide compounds
[0229] Silicon carbide 1
[0230] The prepared porous carbon matrix 1 was placed in a heating device and heated to 500℃ under a positive pressure of 200Pa-500Pa and a heating rate of 1℃ / min in an atmosphere of 20% silane gas and 80% hydrogen gas. The flow rate of the silane gas was controlled at 5 L / min. Nanocrystalline silicon particles were deposited onto the porous carbon matrix to obtain silicon carbide 1. The silicon carbide 1 has the following properties: Dv50 = 8.2 μm, Dv90 = 15.8 μm, (Dv90-Dv10) / Dv50 = 1.68, and SSA = 2.8 μm. 2 / g, the size of the silicon-based particles is d=2nm.
[0231] Silicon carbide 2
[0232] Compared to silicon carbide 1, silicon carbide 2 is prepared from porous carbon matrix 2 through the above process.
[0233] Silicon carbide 3
[0234] Compared with silicon carbide 1, silicon carbide 3 is prepared from porous carbon matrix 3 through the above process, wherein the heating rate is 2℃ / min.
[0235] Silicon carbide 3
[0236] Compared with silicon carbide 1, silicon carbide 3 is prepared from porous carbon matrix 3 through the above process, wherein the heating rate is 2℃ / min.
[0237] Silicon carbide 4
[0238] Compared with silicon carbide 1, silicon carbide 4 is prepared from porous carbon matrix 4 through the above process, wherein the heating rate is 2℃ / min and the temperature is heated to 600℃.
[0239] Silicon carbide 5
[0240] Compared with silicon carbide 1, silicon carbide 4 is prepared from porous carbon matrix 5 through the above process, wherein the heating rate is 5℃ / min and the temperature is heated to 600℃.
[0241] Silicon carbide 6
[0242] Compared with silicon carbide 1, silicon carbide 6 is prepared from porous carbon matrix 6 through the above process, wherein the heating process has a heating rate of 5℃ / min and is heated to 600℃.
[0243] Silicon carbide 7
[0244] Compared with silicon carbide 1, silicon carbide 7 is prepared from porous carbon matrix 7 through the above process, wherein the heating process has a heating rate of 5℃ / min and is heated to 600℃.
[0245] Silicon carbide 8
[0246] Compared with silicon carbide 1, silicon carbide 8 is prepared from porous carbon matrix 8 through the above process, wherein the heating process has a heating rate of 5℃ / min and is heated to 600℃.
[0247] Silicon carbide 9
[0248] Compared with silicon carbide 1, silicon carbide 9 is prepared from porous carbon matrix 9 through the above process, wherein the heating rate is 5℃ / min and the temperature is heated to 600℃.
[0249] Silicon carbide 10
[0250] Compared to silicon carbide 1, silicon carbide 10 is prepared from carbon matrix 1 through the above process, wherein the heating rate is 10℃ / min and the temperature is heated to 600℃.
[0251] Silicon carbide 11
[0252] Compared to silicon carbide 1, silicon carbide 11 is prepared from carbon matrix 2 through the above process, wherein the heating rate is 10℃ / min and the temperature is heated to 600℃.
[0253] II. Preparation of Secondary Cells
[0254] Preparation of II-I positive electrode sheet
[0255] Lithium iron phosphate (LiFePO4), a positive electrode active material, acetylene black (acetylene black), and polyvinylidene fluoride (PVDF) (a binder) were dissolved in N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5. The mixture was stirred thoroughly to obtain a positive electrode slurry. The positive electrode slurry was then uniformly coated onto aluminum foil used as a positive electrode current collector, and subsequently dried, cold-pressed, and slit to obtain the positive electrode sheet.
[0256] Preparation of II-II negative electrode sheet
[0257] The negative electrode active material, silicon-carbon composite material, conductive agent, acetylene black, binder, styrene-butadiene rubber (SBR), and thickener, sodium carboxymethyl cellulose (CMC), are dissolved in deionized water at a mass ratio of 90:4:4:2 and mixed evenly to obtain a negative electrode slurry. The negative electrode slurry is uniformly coated onto the negative electrode current collector copper foil once or multiple times, and then dried, cold-pressed, and slit to obtain the negative electrode sheet.
[0258] The above-mentioned silicon-carbon composite materials 1-11 are used to prepare electrodes corresponding to negative electrode 1-11.
[0259] Preparation of II-III electrolyte
[0260] In an argon atmosphere, organic solvents EC and DMC are mixed evenly at a volume ratio of 1:1. 1M LiPF6 is added and dissolved in the organic solvent. 10% fluoroethylene carbonate FEC is added as an additive. After mixing evenly, an electrolyte is obtained.
[0261] Assembly of II-III secondary batteries
[0262] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to isolate them. The stacked components are then wound to form an electrode assembly. The electrode assembly is placed in the battery casing, dried, and then injected with electrolyte. After formation and settling processes, the secondary batteries in the different embodiments and comparative examples are obtained.
[0263] Example 1: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 1, and electrolyte according to the above method is Example 1.
[0264] Example 2: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 2, and electrolyte according to the above method is Example 2.
[0265] Example 3: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 3, and electrolyte according to the above method is Example 3.
[0266] Example 4: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 4, and electrolyte according to the above method is Example 4.
[0267] Example 5: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 5, and electrolyte according to the above method is Example 5.
[0268] Example 6: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 6, and electrolyte according to the above method is Example 6.
[0269] Example 7: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 7, and electrolyte according to the above method is Example 7.
[0270] Example 8: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 8, and electrolyte according to the above method is Example 8.
[0271] Example 9: The secondary battery obtained by assembling the positive electrode, separator, negative electrode 9, and electrolyte according to the above method is Example 9.
[0272] Comparative Example 1: The secondary battery assembled by the above method with positive electrode, separator, negative electrode 10 and electrolyte is Comparative Example 1.
[0273] Comparative Example 2: The secondary battery assembled by the above method with positive electrode, separator, negative electrode 11 and electrolyte is Comparative Example 2.
[0274] The product parameters for different embodiments are detailed in Table 1. Table 1: Product parameters of comparative examples and embodiments
[0275] Next, the testing process for relevant parameters and battery performance will be explained.
[0276] III. Parameter and Battery Performance Testing
[0277] Test of resistivity of III-I powder
[0278] Weigh a certain mass of silicon-carbon composite material, adjust the depth of the feeding chamber, add the sample into the feeding chamber, apply pressure, manually collect data, and record the powder resistivity test results at different pressure points.
[0279] III-II DCR Test
[0280] At 25℃, the secondary battery was charged to 4.3V at a constant current of 0.33C, then charged at a constant voltage of 4.3V until the current was less than 0.05C, and then discharged to 2V at a current of 0.33C. The actual capacity C0 of the cell was measured. The battery was then charged again to 3.65V at a constant current of 0.33C, then charged at a constant voltage of 3.65V until the current was less than 0.05C. After discharging at a current of 1C0 for 30 minutes, the cell charge was adjusted to 50% SOC. The positive and negative probes of a TH2523A AC internal resistance tester were then connected to the positive and negative terminals of the battery, and the DCR value at 25℃-50% SOC was obtained using the internal resistance tester.
[0281] The battery performance of the comparative and example samples prepared according to the above method was tested, and the test results are detailed in Table 2. Table 2: Battery performance test results for comparative and example cases
[0282] As shown in Tables 1 and 2, in Examples 1-9, by adjusting the preparation parameters for the porous carbon matrix, the material satisfies V 总 / S 总 Within a specific range, this composite material can possess good electrical conductivity and structural stability, thereby improving the energy density of the battery while also enabling the secondary battery to exhibit good cycle performance and low DCR. In the materials of Comparative Examples 1-2, V... 总 / S 总 None of these are within the scope of this application, resulting in relatively poor cycle performance and DCR of the battery.
[0283] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A silicon-carbon composite material, wherein, The silicon-carbon composite material includes: Porous carbon matrix and silicon-based particles; The porous carbon matrix comprises multiple elongated channels with widths ranging from 5 nm to 50 nm. These elongated channels enable the porous carbon matrix to form a cross-linked three-dimensional network structure. The silicon-based particles are distributed within these channels, and the porous carbon matrix satisfies the following condition: 2.2 × 10⁻⁶. -7 ≤V 总 / S 总 ≤10.0×10 -7 ;in, S 总 The total surface area occupied by the channels with widths of 5 nm to 50 nm, measured in cm². 2 / g; V 总 The total pore volume occupied by the channels with a width of 5 nm-50 nm, measured in cm. 3 / g, The porous carbon matrix has a powder resistivity of 1 Ω·cm-300 Ω·cm under 4 MPa pressure, and the silicon-based particles have a content of 25%-65% in the silicon-carbon composite material.
2. The silicon-carbon composite material according to claim 1, wherein, 2.2×10 -7 ≤V 总 / S 总 ≤8.0×10 -7 。 3. The silicon-carbon composite material according to claim 2, wherein, 2.2×10 -7 ≤V 总 / S 总 ≤5.0×10 -7 。 4. The silicon-carbon composite material according to claim 1, wherein, 1×10 4 ≤S 总 ≤50×10 4 Unit of measurement: cm 2 / g.
5. The silicon-carbon composite material according to claim 4, wherein, 1×10 4 ≤S 总 ≤30×10 4 Unit of measurement: cm 2 / g.
6. The silicon-carbon composite material according to claim 1, wherein, 0.002≤V 总 ≤0.250, unit of measurement: cm 3 / g.
7. The silicon-carbon composite material according to claim 6, wherein, 0.004≤V 总 ≤0.200, unit of measurement: cm 3 / g.
8. The silicon-carbon composite material according to claim 1, wherein, The powder resistivity of the porous carbon matrix at 4 MPa pressure is 1 Ω·cm-100 Ω·cm.
9. The silicon-carbon composite material according to claim 1, wherein, The volumetric particle size distribution Dv of the porous carbon matrix 50 ≤10μm; and / or, The volumetric particle size distribution Dv of the porous carbon matrix 90 ≤20μm.
10. The silicon-carbon composite material according to claim 9, wherein, The volumetric particle size distribution Dv of the porous carbon matrix 50 Satisfying 5μm≤Dv 50 ≤10μm; and / or, The volumetric particle size distribution Dv of the porous carbon matrix 90 Satisfying 10μm≤Dv 90 ≤15μm.
11. The silicon-carbon composite material according to claim 1, wherein, The size of the silicon-based particles is less than or equal to 20 nm.
12. The silicon-carbon composite material according to claim 11, wherein, The silicon-based particles have a size of 2nm-10nm.
13. The silicon-carbon composite material according to claim 1, wherein, The content of silicon-based particles in the silicon-carbon composite material is 35%-45%.
14. The silicon-carbon composite material according to claim 1, wherein, The silicon-carbon composite material has a powder resistivity of R ≤ 300 Ω·cm at a pressure of 12 MPa; and / or The resistivity of the silicon-carbon composite material at 16 MPa pressure is R ≤ 200 Ω·cm.
15. The silicon-carbon composite material according to claim 1, wherein, The silicon-carbon composite material has a powder resistivity of 1 Ω·cm-200 Ω·cm at a pressure of 12 MPa; and / or The powder resistivity of the silicon-carbon composite material at 16 MPa pressure is 1 Ω·cm-100 Ω·cm.
16. The silicon-carbon composite material according to claim 1, wherein, The silicon-carbon composite material satisfies one or more of the following (1)-(6): (1) The volumetric particle size distribution Dv of the silicon-carbon composite material 10 ≤5μm; (2) The volume particle size distribution Dv of the silicon-carbon composite material 50 ≤10μm; (3) The volume particle size distribution Dv of the silicon-carbon composite material 90 ≤20μm; (4) The volumetric particle size distribution of the silicon-carbon composite material satisfies: (Dv 90 -Dv 10 ) / D v50 ≤1.8; (5) The compaction density of the silicon-carbon composite material under 2 MPa pressure is 1 g / cm³. 3 -1.5g / cm 3 ; (6) The specific surface area SSA of the silicon-carbon composite material is 2m². 2 / g-10m 2 / g.
17. The silicon-carbon composite material according to claim 16, wherein, The silicon-carbon composite material Satisfy one or more of the following conditions (1)-(6): (1) The volumetric particle size distribution of the silicon-carbon composite material satisfies 3≤Dv 10 ≤5μm; (2) The volumetric particle size distribution of the silicon-carbon composite material satisfies 5 ≤ Dv 50 ≤10μm; (3) The volumetric particle size distribution of the silicon-carbon composite material satisfies 10 ≤ Dv 90 ≤15μm; (4) The volumetric particle size distribution of the silicon-carbon composite material satisfies 1.5 ≤ (Dv) 90 -Dv 10 ) / Dv 50 ≤1.7; (5) The compaction density of the silicon-carbon composite material under a pressure of 2 MPa is 1.1 g / cm³. 3 -1.3g / cm 3 ; (6) The specific surface area SSA of the silicon-carbon composite material is 3m². 2 / g-7m 2 / g.
18. A method for preparing the silicon-carbon composite material according to any one of claims 1-17, wherein, The preparation method includes: The substrate and the pore-forming agent are mixed in a solvent to obtain a first mixture; The first mixture was subjected to high-temperature treatment to obtain a porous carbon matrix; The silicon-carbon composite material is obtained by depositing silane gas onto the porous carbon matrix via chemical vapor deposition.
19. The preparation method according to claim 18, wherein, The substrate includes at least one of sugar and resin.
20. The preparation method according to claim 19, wherein, The sugar includes at least one of glucose, sucrose, fructose, starch, lignin, and dextrin.
21. The preparation method according to claim 19, wherein, The resin includes at least one of linear phenolic resin, epoxy resin, and polyurethane.
22. The preparation method according to claim 18, wherein, The pore-forming agent includes at least one of sodium chloride, potassium chloride, zinc chloride, sodium carbonate, and potassium carbonate.
23. The preparation method according to claim 18, wherein, The mass ratio of the substrate to the pore-forming agent is 1:5-10:
1.
24. The preparation method according to claim 22, wherein, The mass ratio of the substrate to the pore-forming agent is 2:1 to 5:
1.
25. The preparation method according to claim 18, wherein, The solvent includes water or an alcohol, wherein the alcohol includes at least one of methanol, ethanol, ethylene glycol, polyethylene glycol, glycerol, isopropanol, or a polyol.
26. The preparation method according to claim 18, wherein, The mass ratio of the substrate to the solvent is 1:100-10:
1.
27. The preparation method according to claim 26, wherein, The mass ratio of the substrate to the solvent is 1:2-10:
1.
28. The preparation method according to claim 18, wherein, The step of mixing the substrate and the porogen in a solvent includes: mixing the substrate and the porogen in the solvent by stirring.
29. The preparation method according to claim 28, wherein, The stirring speed is 100rpm-1500rpm.
30. The preparation method according to claim 29, wherein, The stirring speed is 200 rpm to 1000 rpm.
31. The preparation method according to claim 18, wherein, The high-temperature treatment of the first mixture to obtain a porous carbon matrix includes: The first mixture is treated at a first temperature to obtain a second mixture, wherein the second mixture is a solid mixture; The second mixture was treated at a second temperature to obtain a carbon precursor; The porous carbon matrix is obtained by treating the carbon precursor at a third temperature.
32. The preparation method according to claim 31, wherein, The first temperature, the second temperature, and the third temperature satisfy one or more of the following (I)-(III): (I) The first temperature is 40℃-80℃; (II) The second temperature is 100℃-200℃; (III) The third temperature is 600℃-1200℃.
33. The preparation method according to claim 32, wherein, The first temperature, the second temperature, and the third temperature satisfy one or more of the following (I)-(III): (I) The first temperature is 40℃-60℃; (II) The second temperature is 130℃-180℃; (III) The third temperature is 800℃-1000℃.
34. The preparation method according to claim 31, wherein, The preparation method includes: crushing the second mixture before treating the second mixture at the second temperature.
35. The preparation method according to claim 31, wherein, The preparation method further includes: crushing the carbon precursor before treating it at the third temperature.
36. The preparation method according to claim 35, wherein, After being crushed, the carbon precursor has a particle size of 1μm-1000μm.
37. The preparation method according to claim 36, wherein, After being crushed, the carbon precursor has a particle size of 5μm-100μm.
38. The preparation method according to claim 31, wherein, The treatment of the carbon precursor at the third temperature includes: treating the carbon precursor in an inert gas at the third temperature.
39. The preparation method according to claim 38, wherein, The inert gas includes at least one of nitrogen, argon, and helium.
40. The preparation method according to claim 18, wherein, The preparation method further includes: before depositing silicon-based particles in the porous carbon matrix, performing impurity removal and / or demagnetization treatment on the porous carbon matrix.
41. The preparation method according to claim 18, wherein, The atmosphere for the chemical vapor deposition is a mixture of silane gas and hydrogen gas.
42. The preparation method according to claim 41, wherein, The volume of the silane gas accounts for 10%-50% of the volume of the mixed gas.
43. The preparation method according to claim 18, wherein, The flow rate of the silane gas used in the chemical vapor deposition is 0.5 L / min - 1 L / min; and / or, The temperature for chemical vapor deposition is 500℃-800℃.
44. A secondary battery, comprising a negative electrode, wherein, The negative electrode sheet comprises a silicon-carbon composite material as described in any one of claims 1-17, or a silicon-carbon composite material prepared by the method according to any one of claims 18-43.
45. An electrical appliance, wherein, The electrical device includes the secondary battery as described in claim 44.
Citation Information
Patent Citations
Porous carbon silicon composite material and preparation method thereof
CN103840140A
Negative pole piece, electrochemical device comprising negative pole piece and electronic device
CN114127985A